Efektifitas Daya Hambat Ekstrak Kulit Buah Naga Merah Konsentrasi 25% dan 50% Terhadap Pembentukan Plak - Lisnayetti Lisnayetti; Nova Herawati; Yustina Sriani; Yessi Yuzar; Syukra Alhamda (Poltekkes Kemenkes Padang, 2022)
One of the ways to control the formation of plaque is by acting chemically. Flavonoids are antibacterial compounds that can inhibit the growth of Streptococcus mutants. The flavonoid content in dragon fruit peel has been shown to inhibit the growth of Streptococcus mutants. The purpose of this study was to determine the effect of gargling 25% and 50% red dragon fruit peel extract on plaque formation. The research design used was True Experimental Design with the design of The Randomized Posttest Only Control Group, with the number of research samples consisting of 3 groups, namely 2 treatment groups and 1 control group. Data were collected by examining the Plaque Index. The analysis used paired t-test (paired test) α <0.05. The results showed that the mean difference in plaque index before and after rinsing with red dragon fruit peel extract, the concentration of 25% was 0.50 + 0.42, while for the red dragon fruit peel extract solution the concentration of 50% was 0.83 + 0.74 and chlorhexidine. 0.83 + 0, 57. This shows that the red dragon fruit peel extract with a concentration of 25% is more effective in suppressing plaque growth than the 50% concentration of dragon fruit peel extract. Red dragon fruit peel extract with a concentration of 25% can be recommended as a basic ingredient of herbal mouthwash for the prevention of dental and oral diseases.